2021
DOI: 10.1371/journal.pone.0243908
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review to map the concept, content, and outcome of wilderness programs for childhood cancer survivors

Abstract: Objectives Systematic mapping of the concept, content, and outcome of wilderness programs for childhood cancer survivors. Design Scoping review. Search strategy Searches were performed in 13 databases and the grey literature. Included studies describe participation of childhood cancer survivors in wilderness programs where the role of nature had a contextual and therapeutic premise. At least two authors independently performed screening, data extraction and analysis. Results Database searches yielded 184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 66 publications
1
33
0
Order By: Relevance
“…18 19 The majority of nature-based programmes that specifically address the needs of childhood and AYA cancer survivors can be categorised under the umbrella term of adventure programmes. 20 A previous observational study involving a 6-day outdoor adventure programme demonstrated improved body image, selfcompassion, self-esteem and decreased depression and alienation in young adult cancer survivors compared with a wait-list control. 21 Another observational study reported that a 1-week outdoor adventure camp significantly enhanced physical activity and reduced sedentary behaviour of young adult cancer survivors compared with wait-list controls up to 3 months after camp.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 92%
See 2 more Smart Citations
“…18 19 The majority of nature-based programmes that specifically address the needs of childhood and AYA cancer survivors can be categorised under the umbrella term of adventure programmes. 20 A previous observational study involving a 6-day outdoor adventure programme demonstrated improved body image, selfcompassion, self-esteem and decreased depression and alienation in young adult cancer survivors compared with a wait-list control. 21 Another observational study reported that a 1-week outdoor adventure camp significantly enhanced physical activity and reduced sedentary behaviour of young adult cancer survivors compared with wait-list controls up to 3 months after camp.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 92%
“…A recently published systematic scoping review that mapped the concept, content and outcome of wilderness programmes for childhood cancer survivors concluded that high-quality studies with appropriate comparison groups are needed to further build the evidence base for these programmes. 20 Therefore, the present study is initiated to examine the feasibility of performing a randomised clinical trial (RCT) of a wilderness programme that is specifically developed to benefit the health of AYAs that are diagnosed with cancer during childhood, adolescence or young adulthood. A holiday programme is chosen as a comparison to control for other possible effective factors such as attention, group support and getting out of their regular environment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The results were then followed by an analysis of the text words (title, abstract, or authors keywords) of the retrieved articles, and of the index terms (subject heading words) used to describe the articles. An earlier review was also examined for words for the search concepts of wilderness-related therapies [27], followed by discussions and comments from all team members.…”
Section: Search Strategymentioning
confidence: 99%
“…One way to nurture independence in adolescents is to provide proper encouragement and reinforcement to explore the world on their own and take responsibility for their decisions in a safe setting [ 8 ]. Wilderness programs adopt this approach and immerse participants to experience mental, physical, emotional, and spiritual challenges, such as survival challenges and long-term parental separation, in a safe and supportive outdoor environment [ 9 , 10 ]. A review of the solo wilderness programs reported that participants gain greater sense of independence by being free from manipulation and domination from others [ 11 ].…”
Section: Introductionmentioning
confidence: 99%